Rotordynamic Fluid Force Moments on an Open-type Centrifugal Compressor Impeller in Precessing Motion - Yoshiki Yoshida; Yoshinobu Tsujimoto; Daizo Yokoyama; Hideo Ohashi; Fumitaka Kano (International Journal of Rotating Machinery)
In recent years, increasing interest has been given to the rotordynamic fluid forces on impellers, from the view point of the shaft vibration analysis. Previous experimental and analytical results have shown that the fluid-induced forces and moments on closed type pump impellers contribute substantially to the potential destabilization of subsynchronous shaft vibrations. However, to date few papers are known of the rotordynamic fluid forces on open-type centrifugal impellers. This paper reports about experimental investigations of the rotordynamic fluid force moments on an open-type centrifugal compressor impeller in precessing motion. For open-type impellers, the variations of the tip clearance and the clearance between the back shroud and casing due to the precessing motion contribute to the rotordynamic fluid force moments. Experiments were conducted to measure the rotordynamic fluid force moments directly using the 4-axis sensor, and the unsteady pressure on the front and back casing wall. In this paper, following results are obtained: (1) The fluid force moment becomes destabilizing in the region of negative precessing speed ratio (-0.3<Ω/ω<0), at the design flow rate; (2) At reduced flow rate, the destabilizing fluid force moments occurred at small positive precessing speed ratio (0.2<Ω/ω<0.4); (3) From the comparison of direct measured fluid force moments with those estimated from the unsteady pressure measured on the front and back casing walls, it was found that the destabilizing moments in the backward precession are mainly caused by the fluid forces on the front surface of the present impeller, where there is large clearance between the back shroud and casing.